Desain Perancangan Troli Ergonomi Bagi Pekerja Material Handling UMKM Sigma Motor. - Andersona , Kevin Ferdinand; Hanggara, Fuad Dwi; Adi Nugroho (Greeners: Journal of Green Engineering for Sustainability, 2023)
The development of the industrial sector requires researchers to continue in innovate, from anindustrial management system, workflow design, to product innovation. There are so manyinnovations from products that are created to make it easier for users to do their work. But still,there are many MSMEs that still use human energy to do certain jobs, one of which is liftingand carrying loads manually or commonly referred to as Manual Materials. Handling (MMH).In one case of the MSMEs spare part distributor "Sigma Motor", it was found that the workersstill use Manual Material Handling, and this material handling is done repeatedly with thedistance that they must travel in 8 meters. With this distance each worker per minute can manageto transport 3 boxes at a time. This has an impact on reduced work productivity, the emergenceof pain in workers both temporary and permanent, increasing the possibility of accidents. Thisstudy uses the Nordic Body Map (NDM) method to analyze the most common complaints andthe Rapid Entire Body Assessment (REBA) method to analyze worker posture. As well asanthropometric measurements to determine the dimensions of the trolley design for proposal toMSMEs. This study aims to determine complaints of pain, worker posture when handlingmaterials, and existing risks. Also, to design a trolley for proposal to MSMEs with ergonomicsstudies. With the proposal design trolley, hope that can help workers in transporting boxes ofgoods from the loading area to container trucks and in other way. So, the result of this researchis to change a work process on MSMEs in material handling by using tools from the trolleydesign as a suggestion to MSMEs to help workers in material handling.